IMPLEMENTATION OF EDUCATIONAL OPERATIONAL ASSISTANCE (BOP) FUND MANAGEMENT IN EDUCATIONAL INSTITUTIONS - Dewi Septiani Dewi (PT. Sulthan Journal Publisher, 2026)
The management of Educational Operational Assistance (BOP) funds plays a crucial role in supporting the sustainability of educational institutions. However, in practice, several schools and educational institutions have not fully implemented proper management functions in managing BOP funds. For instance, some institutions do not conduct systematic budget planning and lack written budget plans that can serve as detailed references for financial management. Consequently, financial expenditures are often conducted incidentally without clear budgeting guidelines. This study aims to analyze the implementation of BOP fund management in educational institutions, particularly in terms of planning, budgeting, implementation, and supervision. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the implementation of BOP fund management has not been carried out optimally in several aspects, including planning, budgeting, implementation, and supervision. Therefore, improvements are required to ensure more effective and accountable financial management. One of the main challenges in BOP fund management is the limited quality of human resources, both in terms of academic qualifications and managerial competencies.